Pengembangan Model Pembelajaran Inquiry Berbasis Saintifik Terhadap Kemampuan Berpikir Kritis Siswa - Devi Afriyuni Yonanda (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2019)
This research is based on the problem of still low critical thinking skills of elementary school students. Students in the learning process are still required to memorize facts, concepts, and theories on the material they study. The purpose of this study is to improve students' critical thinking skills through a Scientific Based Inquiry models (IBS). The type of research used is Research and Development (R & D) or research and development. The research procedure used the Borg & Gall model. Product validation tests are carried out by a team of experts or material experts, linguists, and practitioners. Practicality test is carried out by using questionnaire responses of teachers and students after the learning process. Effectiveness testing on limited trials using experimental design pretest-posttest control group design. The results of this development study obtained product validity test obtained a score of 3.4 with the criteria of